A connectionist computational method for face recognition - Pujol, Francisco A.; Mora, Higinio; Girona-Selva, José A. (Zielona Góra: Uniwersytet Zielonogórski)
In this work, a modified version of the elastic bunch graph matching (EBGM) algorithm for face recognition is introduced. First, faces are detected by using a fuzzy skin detector based on the RGB color space. Then, the fiducial points for the facial graph are extracted automatically by adjusting a grid of points to the result of an edge detector. After that, the position of the nodes, their relation with their neighbors and their Gabor jets are calculated in order to obtain the feature vector defining each face.
Keywords: pattern recognition; face recognition; neural networks; self-organizing maps